2015
DOI: 10.1155/2015/381704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bottom Ash Replacements as Fine Aggregate on the Property of Cellular Concrete with Various Foam Contents

Abstract: This research focuses on evaluating the feasibility of utilizing bottom ash from coal burning power plants as a fine aggregate in cellular concrete with various foam contents. Flows of all mixtures were controlled within 45 ± 5% and used foam content at 30%, 40%, 50%, 60%, and 70% by volume of mixture. Bottom ash from Mae Moh power plant in Thailand was used to replace river sand at the rates of 0%, 25%, 50%, 75%, and 100% by volume of sand. Compressive strength, water absorption, and density of cellular concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 17 publications
0
14
0
3
Order By: Relevance
“…The final objective of this study is to discuss effective soft soil improvement techniques. Based on literature and observations through some historical cases, preloading and prefabricated vertical drains [136,138] and geofoam as lightweight fill materials [145,146] are widely used today. The study found that both techniques are environmentally friendly.…”
Section: Discussion and Future Research Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The final objective of this study is to discuss effective soft soil improvement techniques. Based on literature and observations through some historical cases, preloading and prefabricated vertical drains [136,138] and geofoam as lightweight fill materials [145,146] are widely used today. The study found that both techniques are environmentally friendly.…”
Section: Discussion and Future Research Developmentmentioning
confidence: 99%
“…Therefore, the unconfined compressive strength is dependent on the mixed material used. The material mixture used in cellular concrete as foam content + bottom ash [146], flue ash [147] and aluminium powder [148] produces a compressive strength of 0.8-5.2 MPa, 1.7-2.7 MPa and 0.9-7.9 MPa, respectively. The use of geofoam is well received because it is more practical as a readily-available source, and there are many manufacturers and suppliers around the world [149].…”
Section: Geofoam As Lightweight Fill Materialsmentioning
confidence: 99%
“…is type of concrete is a new type of geotechnical material developed in recent years and possesses the advantages of low weight, stable performance, convenient construction, and so forth. [4][5][6][7]. e applications of cast-in-situ foamed concrete have expanded considerably in civil engineering as a result of scientific and technical advances in its production.…”
Section: Introductionmentioning
confidence: 99%
“…Onprom et al [1], Ghafoori and Bucholc [2], Aggarwal et al [3], Andrade et al [4], and Bai et al [5] experimentally tested the influence of bottom ash as a substitute for natural sand in concrete. Zhu et al [6] experimentally determined the influence of iron ore tailings as fine aggregate on the concrete.…”
Section: Introductionmentioning
confidence: 99%